2009
DOI: 10.4049/jimmunol.0803783
|View full text |Cite
|
Sign up to set email alerts
|

B7-1/2 (CD80/CD86) Direct Signaling to B Cells Enhances IgG Secretion

Abstract: B cell responses are regulated by Ag recognition, costimulatory signals provided by interaction with helper T cells, and by innate signals. We recently provided evidence for a link between the effects of innate and costimulatory signals on B cells during influenza virus infection, by demonstrating that most B cells in the regional lymph nodes of the respiratory tract enhance surface expression of the costimulator B7-2 (CD86) within 24–48 h following infection via a type I IFNR-dependent mechanisms, a finding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 49 publications
5
83
0
Order By: Relevance
“…7B). However, IL-4 expression levels overall were very low, consistent with a predominant switch of B cells to IgG2a/c but not IgG1 after influenza virus infection (36). Together, the data show X5 ϩ /X4 ϩ -expressing T GC to be most closely associated with the functions and phenotypes thought to characterize their functions.…”
Section: Cxcr4mentioning
confidence: 65%
See 1 more Smart Citation
“…7B). However, IL-4 expression levels overall were very low, consistent with a predominant switch of B cells to IgG2a/c but not IgG1 after influenza virus infection (36). Together, the data show X5 ϩ /X4 ϩ -expressing T GC to be most closely associated with the functions and phenotypes thought to characterize their functions.…”
Section: Cxcr4mentioning
confidence: 65%
“…B cell proliferation. Magnetically activated cell sorting (MACS)-enriched, CFSE-labeled B cells at 6.25 ϫ 10 6 cells/ml were pulsed with 1,000 HAU/ml influenza virus A/Mem/71 in culture medium (36) for 3 h at 37°C. A total of 2.5 ϫ 10 5 pulsed B cells were cocultured in 96-well roundbottom plates for 4 days with graded numbers of purified CD4 T cell subsets from MedLN of infected mice in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…84 CTLA4-Ig binds to CD80/ CD86 molecules on dendritic cells and promotes the induction of the immunomodulatory enzyme indoleamine 2,3 dioxygenase 85,86 and the tolerogenic molecule HLA-G. 87 Experimental data suggest that reverse signaling of CD80/ CD86 also exists in B cells. 88,89 It is, therefore, tempting to speculate that, when belatacept binds to CD80/CD86, it directly influences the B cell fate. This mechanism could account for the recent observation that the frequency and absolute number of CD19…”
Section: Belataceptmentioning
confidence: 99%
“…on May 13, 2018. by guest www.bloodjournal.org From CD40L interactions have been reported important for GC formation and class switching. [14][15][16] We found that immunization with A␤1-15 liposomes induced strong anti-A␤ IgM and IgG responses both in the CD28-and CD40L-deficient mice ( Figure 3A-B). Again, predominance of IgG2b and TI-associated IgG3 similar to that observed in WT mice ( Figure 3C-E).…”
mentioning
confidence: 94%